Factors influencing consumers' trust on e-commerce adoption in sri lanka - Ilmudeen, A. (university of Jaffna, 2014)
The purpose of the research is to find the factors which persuade the consumers' trust on e commerce adoption in Sri Lanka. The creation of the Internet has reduced physical borders and made the world a smaller place where people can able to keep in touch with one another at any time from every nook and corner. This research arise the following research questions. How the security and privacy concerns in online transaction relate with e-commerce adoption? How do the trustworthiness and reliability of the web vendors relate to the consumer's adoption of e commerce? and How the performance, physical, security, privacy and delivery risk affect consumers to adopt in e-commerce. Questionnaire was used as a research instrument and basically the questionnaire cover two parts; such as 1st part covers questions related to online purchase and adoption of electronic commerce. The 2nd part covers factors affecting e-commerce security, privacy, and trust as well as risk perceptions. The extensive literature survey helped to form the research variables and hypothesis. To measure the questions likert scale measurement was used. The likert scale measurement were ranging from 1 - very unimportant to 5 - very important. This research shows that, consumer's perceived privacy, security and trustworthiness of Web vendor in e-commerce transaction positively contributes to his/her trust in e-commerce adoption. On the other hand the influence of a consumer's perceived security in e-commerce transaction is mediated by consumer's perceived privacy and consumer's adoption in e-commerce transaction not negatively associated with e-commerce perceived risks.
Keywords: Internet; E-commerce; Security; Risk; Consumer